(untitled) (Economics and region, 2021)
The purpose of the article is to study the features of gastronomy as a factor in the formation of competitive advantages of cultural tourism services. The authors determined that gastronomic services are used in many areas of tourism and leisure, including in the form of catering services during the trip, as well as a separate purpose for travel to learn the cuisine of a particular city or region, the country as a whole. The article examines the main approaches to defining the essence of the concept of "gastronomic tourism". It is stated that the concept "gastronomic tourism" must be understood as an integral part of a trip or journey. As a result of the study, the main components of gastronomic tourism were identified, which characterize its content as a type of cognitive tourist leisure: cultural consumption; self-education; informal communication; satisfaction of gastronomic needs; cognitive activity and the like. The types of gastronomic tourism are analyzed on the basis of various classification features. The component of culinary activity in the socio-cultural life of a person is expressed in the defeat, emotions, condition, covering the tourist during the holiday. Based on these reactions, the tourist feels, comprehends the culinary features, assesses the gastronomic features of the area and the food services provided. Prospects for further research are to identify potential directions for the development of gastronomy in the field of tourism, improving its quality and service, taking into account the needs of modern consumers of tourism products.